The Influence of Leadership, Smart Posyandu and Service Quality on Patient Satisfaction at Public Health Centers in Tomohon City - Aror, Gerald Anthon; Wullur, Norry HY; Wullur, Ivan Soepardja Gustaf (Abdurrauf Science and Society, 2025)
This study aims to determine how much there is or is not a positive and significant relationship between: (1). Leadership of the head of the health center with patient satisfaction, (2). Smart Posyandu with patient satisfaction, (3). Quality of health services with patient satisfaction, Together the leadership of the head of the health center, smart Posyandu and quality of service together with patient satisfaction. This study uses a survey method with correlational analysis which aims to obtain data on patient satisfaction variables to obtain data on the variables of leadership, smart Posyandu and quality of service used data sources from patients of each health center in Tomohon City. The number of samples was set at 320 people from a population of 3922 patients. By using simple correlation analysis and multiple correlation analysis at error levels of 0.05 and 0.01, it was concluded that the variables of leadership of the head of the health center (Xl), smart integrated health post (X2), and quality of service (X3), both individually and together, have a positive and significant relationship with patient satisfaction (Y).